(3Md eTcdGJ GdETGQGJs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3faY ajgG Ydi fSHI eNJdaI eYOI fMh Ndb eNJda HMSH GdeYOfjGJ hGdfHGJ hGdMjhGf s
(3BNQgG (B:s
(3hCfG CJhbY eef jbY Gdjg cJGHi gPG Cf jUdM eG jYKQ Ydjg ef GdMdd hGdaSGO s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs